Effects of cooling and interval cleaning on the performance of soiled photovoltaic panels in Muscat, Oman - Girma T. Chala; Shaharin A. Sulaiman; Shamsa M. Al Alshaikh (Results in Engineering, 2024)
Due to the present alarming environmental problem, the world has turned to photovoltaic (PV) solar energy as a sustainable, renewable, and environmentally friendly alternative. Solar energy technology has rapidly improved in recent decades, and the global installation of photovoltaic systems has been increasing at a rate of 24% annually. However, soiling on panels and high panel temperature affect the performance of photovoltaic systems, and this leads to significant production loss, especially in the Middle East, where the dust intensity and ambient air temperature are at their highest levels. This paper presents the influence of cooling and interval cleaning on the performance of the photovoltaic system installed in Muscat, Oman. The study involved cleaning the first panel at a comparable inclination angle. The second panel had its inclination angle changed. The third panel was designed to inject water for cooling purposes. In this case, the panel was subjected to water injection for 30 s once per week, followed by daily water injection for 120 s in the second week. All the results were compared with the fourth panel, which was neither cleaned nor touched. Measurements, including open circuit voltage, short circuit current, solar panel temperature, solar radiation, and power, were made in 1-min intervals using a data logger. The results of the experiment showed that cleaning the panel manually every three days resulted in the highest output power and efficiency, reaching 85.6 W with 23.6% efficiency. The cooling of the panel resulted in an increase in power, especially for the longer injection duration. Conclusively, water injection resulted in an energy output growth of 23.9%.